THE ROLE OF THE CONSUMER DISPUTE RESOLUTION AGENCY IN BREACH OF PERFORMANCE DISPUTES UNDER THE CONSUMER PROTECTION LAW - Yuwono, Excel Febrianka; Putra, Moody R. Syailendra (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Globalization and modern economic development not only bring opportunities but also generate new challenges in the relationship between consumers and business actors. One of the dispute resolution mechanisms regulated under Law No. 8 of 1999 on Consumer Protection is the Consumer Dispute Resolution Agency as a non-litigation forum. This study aims to analyze the Consumer Dispute Resolution Agency’s authority in adjudicating default disputes and the implications of Supreme Court Decision No. 275 K/Pdt.Sus-BPSK/2024 for consumer protection. The research method applied is normative juridical with statutory, conceptual, and case study approaches. The findings reveal that the Consumer Dispute Resolution Agency is authorized to resolve consumer disputes through mediation, arbitration, or conciliation, but not pure contractual defaults, which fall under the jurisdiction of civil courts. The Supreme Court decision confirms that default disputes in sales contracts cannot be categorized as consumer disputes, thereby excluding the Consumer Dispute Resolution Agency’s jurisdiction. This situation creates challenges because consumers who suffer losses due to default cannot obtain optimal protection through the Consumer Dispute Resolution Agency. Moreover, the lack of executorial power for the Consumer Dispute Resolution Agency decisions further undermines its effectiveness as a quasi-judicial body. Therefore, strengthening regulations and harmonizing the Consumer Protection Law with civil law are essential to ensure that the Consumer Dispute Resolution Agency can function more effectively in providing legal certainty and consumer protection.